2005
DOI: 10.1111/j.1460-9568.2005.03891.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay of myelin formation in arylsulphatase A‐deficient mice

Abstract: Metachromatic leukodystrophy (MLD) is a lysosomal storage disorder caused by the deficiency of arylsulphatase A (ASA). This leads to the accumulation of the sphingolipid 3-O-sulphogalactosylceramide (sulphatide) and progressive demyelination in the nervous system of MLD patients. The mechanisms and development of pathology in the disease are still largely unknown. In this study we investigate how the inability to degrade sulphatide affects the formation of myelin in ASA-deficient (ASA-/-) mice. In mice at 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…Furthermore, transplantation of MLD OLPs showed that ARSA deficiency did not influence the migratory capacity of the mutant OLPs. This result shows that the pathogenesis of MLD mice is not caused by deficient colonization of white matter territories by endogenous OLPs (Yaghootfam et al, 2005) nor caused by a toxic effect from the MLD brain environment. Instead, it suggests that pathogenesis is caused by a cellautonomous defect of ARSA deficiency after cell migration.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, transplantation of MLD OLPs showed that ARSA deficiency did not influence the migratory capacity of the mutant OLPs. This result shows that the pathogenesis of MLD mice is not caused by deficient colonization of white matter territories by endogenous OLPs (Yaghootfam et al, 2005) nor caused by a toxic effect from the MLD brain environment. Instead, it suggests that pathogenesis is caused by a cellautonomous defect of ARSA deficiency after cell migration.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, it is unclear whether the accumulation of sulfatides in perinatal OLPs in the MLD mouse model, which might still be at a low concentration at the time of the transplantation, has an impact on their survival and/or differentiation. Some recent work elegantly illustrates the role of sphingolipids during oligodendroglial differentiation (Bansal et al, 1999;Hirahara et al, 2004;Yaghootfam et al, 2005). For example, absence of sulfatides stimulates a premature differentiation of OLPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin was purified from total brains by sucrose gradient centrifugation, as described previously (Norton and Poduslo, 1973). Purified myelin, total brain samples, or peripheral nerves (plexus brachialis, sciatic nerve) were homogenized in 20 vol of chloroform/methanol (2:1), and sphingolipids were isolated as described previously (Yaghootfam et al, 2005). Lipid samples were loaded onto silica gel 60 thinlayer chromatography (TLC) plates (Merck) manually or using an automatic TLC sampler (CAMAG, Berlin, Germany) and developed using chloroform/methanol/water (60:27:4, v/v/v) as the solvent system.…”
Section: Methodsmentioning
confidence: 99%
“…Active Myelination in ASA Ϫ/Ϫ Animals-Previous studies performed in ASA Ϫ/Ϫ animals during the peak of myelination showed a delayed expression of mRNA for myelin proteins: MBP, myelin and lymphocyte protein, and PLP, which suggests a defect in the differentiation program of OLs in the ASA Ϫ/Ϫ context (38). We have examined the expression of PDGFR␣ and MBP by immunohistochemistry in the cortex of ASA ϩ/ϩ and ASA Ϫ/Ϫ mice during the period of active myelination at postnatal days 7, 14, and 21 ( Fig.…”
Section: Levels Of Pdgfr␣ and Myelin Proteins Are Reduced Duringmentioning
confidence: 99%